Front Cover: Efficient Capture of Organic Dyes and Crystallographic Snapshots by a Highly Crystalline Amino‐Acid‐Derived Metal–Organic Framework (Chem. Eur. J. 67/2018). Issue 67 (27th September 2018) - Mon, Marta; Bruno, Rosaria; Tiburcio, Estefanía; Casteran, Pierre‐Edouard; Ferrando‐Soria, Jesús; Armentano, Donatella; Pardo, Emilio
Abstract : A novel eco‐friendly water‐stable metal–organic framework, prepared from a derivative of the natural amino acid L‐serine and featuring functional channels, efficiently captures different organic dyes at very low concentrations, similar to those observed in industrial discharges. In addition, single‐crystal X‐ray diffraction offers unprecedented snapshots of the host–guest interactions governing the capture processes. More information can be found in the Full Paper by J. Ferrando‐Soria, D. Armentano, E. Pardo, et al. onpage 17712 .